Factors influencing job satisfaction among academic staffs - Choon Hee Ong; Chong Hui Shi; Tan Owee Kowang; Goh Chin Fei; Lim Lee Ping (International Journal of Evaluation and Research in Education (IJERE), 2020)
The purpose of this study is to examine the relationship between pay and benefits, work environment, top management leadership, workload and job satisfaction among academic staffs in a private academic institution in Malaysia. Motivation-Hygiene Theory, Maslow’s Needs Hierarchy theory and Leader-Member Exchange (LMX) theory were used to establish the theoretical framework of this study. Questionnaire survey method was employed to collect data which yielded 82 responses in this study. Statistical Package for Social Science (SPSS) was used to perform data analysis throughout the study. All study variables were found to have significant positive relationships with job satisfaction among academic staffs in the selected institution. Top management leadership was discovered to have the most significant relationship with job satisfaction. The findings of this research provide a clear message to the top management that leadership plays an important role in enhancing job satisfaction of the academic staffs. Hence, it is suggested that the institution management should adopt appropriate leadership style and establish effective strategies and policies that aim to increase job satisfaction and performance of the academic staffs.